Chemical Composition and Toxicity of Water-Soluble Fractions of Oil Samples from the Extensive Spill in Northeast Brazil - de Santana, Debora Cristina Nascimento [UNESP]; Moreira, Lucas Buruaem [UNESP]; Cruz, Ana Carolina Feitosa [UNESP]; Perina, Fernando Cesar; Lourenço, Rafael André; Abessa, Denis Moledo de Souza [UNESP] (Springer Nature, 2025)
This study evaluated the effects of water-soluble fractions (WSF) of stranded oil sampled from the beaches of Trancoso and Massarandupió (Bahia, Brazil) following a mysterious oil spill along Brazil’s northeast coast (2019–2020). The samples were characterized for aliphatic hydrocarbons (AHs) and polycyclic aromatic hydrocarbons (PAHs) and tested for chronic toxicity in the embryo-larval stages of the sea urchin Echinometra lucunter. The WSFs contained high levels of PAHs, some of which were above the acceptable levels for water in Brazil, and toxicity to sea urchin embryos tended to occur at higher concentrations.
Keywords: Hydrocarbons; Marine ecotoxicology; Marine pollution; Mysterious oil spill; Species sensitivity